老年晚期非小细胞肺癌姑息治疗获益研究进展 (Zhongguo Fei Ai Za Zhi, 2015)
Lung cancer is the leading cause of death among all cancers in China. It also has the highest incidence when compared to other cancers. Almost half of all lung cancers occur over 70-year-old. Approximately 85% of all lung cancers are non-small cell lung cancer (NSCLC). The majority of patients are advanced lung cancer. Due to the unique alterations in physiology, elderly patients are at a greater risk of toxicity from chemotherapy. Palliative care as a special medical care is an important treatment for elderly patients with advanced NSCLC. Low-dose palliative radiotherapy can improve respiratory symptoms in elderly patients with NSCLC, with the tolerated side effects. Elderly patients with epidermal growth factor receptor (EGFR) mutation can benefit from gefitinib and have a good tolerate of erlotiib. Cryocare Surgical System has an increasing trend of application in the treatment of elderly patients with NSCLC. Chinese medicine has effects in improving clinical symptoms and reducing side effects of chemotherapy, it can also improve the quality of life in these patients. Psychosocial support therapy can alleviate the burden of patients with NSCLC to some extent, but needs to improve its systematicness. Assessment and the time of palliative care are two important factors which determine the outcome of patients. We introduce the progress in palliative care benefit of elderly NSCLC, in order to provide the basis for palliative care of elderly NSCLC.